Xanthogranulomatous salpingitis as a rare pathologic aspect of chronic active pelvic inflammatory disease - Nese Yener; Erdin Ilter; Ahmet Midi (Wolters Kluwer Medknow Publications, 2011)
Xanthogranulomatous salpingitis (XGS) is a rare form of chronic inflammation of the fallopian tubes. A 41-year old woman with a history of secondary infertility for 2 years is presented. The patient underwent bilateral salpingooopherectomy with presumptive diagnosis of adnexal mass with cystic component. Intraoperative pathology consultation was done. The diagnosis of bilateral XGS associated with chronic active follicular salpingitis was made. XGS is reported to be caused by an unsuccesfully treated pelvic inflammatory disease. Its association with chronic active follicular salpingitis has not been previously reported. Chronic active follicular salpingitis with xanthogranulomatous inflammation might give the impression of a cystic adnexal mass with septations on preoperative pelvic computed tomography. Frozen sections are necessary to rule out malignancy as done in our case.